2019
DOI: 10.1016/j.ijscr.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A case report of ten-month-neglected anterior shoulder dislocation managed by open reduction combined with Latarjet procedure

Abstract: Highlights Neglected shoulder dislocation is relatively rare case but the management is challenging. Dislocated should be reduced as soon as possible to prevent complicated situation. Latarjet procedure is an effective treatment of choice for neglected shoulder dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The failure rate of closed reduction was high due to soft tissue obstruction (long head of biceps, intra-glenoid scar, or posterior capsular contracture) and osseous block (glenoid fractures or engaging Hill-Sachs lesions), meanwhile the danger of an iatrogenic fracture or neurovascular damage was also high 8,22 . The pathophysiological changes of the chronic anterior shoulder dislocation were different from those of recurrent anterior dislocation, which also limited the application of arthroscopy 6,23,24 . In this study, the duration of dislocation was more than 3 weeks in all cases, and all patients underwent open reduction and stabilization of the involved shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…The failure rate of closed reduction was high due to soft tissue obstruction (long head of biceps, intra-glenoid scar, or posterior capsular contracture) and osseous block (glenoid fractures or engaging Hill-Sachs lesions), meanwhile the danger of an iatrogenic fracture or neurovascular damage was also high 8,22 . The pathophysiological changes of the chronic anterior shoulder dislocation were different from those of recurrent anterior dislocation, which also limited the application of arthroscopy 6,23,24 . In this study, the duration of dislocation was more than 3 weeks in all cases, and all patients underwent open reduction and stabilization of the involved shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Lubis et al managed a case of chronic anterior shoulder dislocation with open reduction and Latarjet procedure. The authors concluded that coracoid osteotomy prevents re-dislocation and enhances the functional status of the shoulder joint [14]. Open reduction along with Latarjet is further supported by the…”
Section: Discussionmentioning
confidence: 84%
“…In the past, patients with chronic dislocations were managed conservatively provided they had a functional range of motion. [16]. They concluded that coracoid osteotomy helps in preventing redislocation and improves the functional status of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%